2021
DOI: 10.1002/ijgo.13987
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women seeking care for abortion complications in health facilities: Secondary analysis of the WHO Multi‐Country Survey on Abortion in 11 African countries

Abstract: Objective: Despite evidence of acute and long-term consequences of suboptimal experiences of care, standardized measurements across countries remain limited, particularly for postabortion care. We aimed to determine the proportion of women reporting negative experiences of care for abortion complications, identify risk factors, and assess the potential association with complication severity. Methods: Data were sourced from the WHO Multi-Country Survey on Abortion for women who received facility-based care for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Widespread negative experiences of care were found, with 62% of women reporting at least one negative experience of care and 56.5% of women with abortion-related complications reporting that they felt anxious/stressed during their facility stay. 9,10 At first glance, this may appear to conflict with the results reported by Eboigbe et al 11 where women reported high levels of satisfaction with care when looking at different components of care individually (>75% reported being satisfied or very satisfied for four out of the five questions related to satisfaction); however, the results of the composite measure for satisfaction showed that nearly 50% of women reported being less than satisfied with at least one element of their care. 11 Women of low socioeconomic status were found to be a particularly vulnerable group in these papers, with higher odds of reporting negative experiences and high odds of reporting feeling anxious or stressed during their facility stay.…”
Section: Quality Of Care For Abortion-related Complications: Insights From the Who Multi-country Survey On Abortion-related Morbidity Acrmentioning
confidence: 78%
See 1 more Smart Citation
“…Widespread negative experiences of care were found, with 62% of women reporting at least one negative experience of care and 56.5% of women with abortion-related complications reporting that they felt anxious/stressed during their facility stay. 9,10 At first glance, this may appear to conflict with the results reported by Eboigbe et al 11 where women reported high levels of satisfaction with care when looking at different components of care individually (>75% reported being satisfied or very satisfied for four out of the five questions related to satisfaction); however, the results of the composite measure for satisfaction showed that nearly 50% of women reported being less than satisfied with at least one element of their care. 11 Women of low socioeconomic status were found to be a particularly vulnerable group in these papers, with higher odds of reporting negative experiences and high odds of reporting feeling anxious or stressed during their facility stay.…”
Section: Quality Of Care For Abortion-related Complications: Insights From the Who Multi-country Survey On Abortion-related Morbidity Acrmentioning
confidence: 78%
“…11 Women of low socioeconomic status were found to be a particularly vulnerable group in these papers, with higher odds of reporting negative experiences and high odds of reporting feeling anxious or stressed during their facility stay. 9,10 As has been outlined by WHO, a multipronged approach including self-care, clinical care, task sharing, human rights, and an enabling legal environment is needed to deliver high-quality abortion and postabortion care including access to family planning, 12 but the evidence presented throughout this Supplement shows that we still have considerable progress to make. Immediate action needs to be taken by healthcare providers and policy makers, and we highlight three key areas here:…”
Section: Quality Of Care For Abortion-related Complications: Insights From the Who Multi-country Survey On Abortion-related Morbidity Acrmentioning
confidence: 99%
“…Research suggests providing family planning counseling and methods at the same time as PAC is best and leads to greater uptake, protecting them from subsequent unintended pregnancies [ 9 , 29 , 30 ]. Other work exploring receipt of PAC among women at facilities across 11 countries in Africa found 62% of women having at least one negative experience of care, which included things like not being able to ask questions during the treatment (34%), not feeling their preferences were followed during receipt of care (18%), not receiving pain medication (13%), and dissatisfaction with privacy and wait time (15% and 22%, respectively) [ 31 ]. These experiences– which were more likely among young women, unmarried women, and those with less education or wealth– offer a potential explanation for why many delay or avoid facility-based PAC even when they are concerned about complications [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other work exploring receipt of PAC among women at facilities across 11 countries in Africa found 62% of women having at least one negative experience of care, which included things like not being able to ask questions during the treatment (34%), not feeling their preferences were followed during receipt of care (18%), not receiving pain medication (13%), and dissatisfaction with privacy and wait time (15% and 22%, respectively) [ 31 ]. These experiences– which were more likely among young women, unmarried women, and those with less education or wealth– offer a potential explanation for why many delay or avoid facility-based PAC even when they are concerned about complications [ 31 ]. Future work examining patient-centered measures of PAC is needed to systematically include this aspect of quality in subsequent research and monitoring of these services.…”
Section: Discussionmentioning
confidence: 99%
“…As such, healthcare deficiencies, which mirror the geographic distribution of emergency obstertic care in the sub-Saharan region more generally [ 25 ], further compound social disparities in maternal health, as population based studies consistenly indicate that women from rural areas or from disadvantaged social backgrounds are less likely to use contraception to prevent an unintended pregnancy and more likely to rely on unsafe means to terminate a pregnancy when seeking an abortion. Previous studies have also indicated that the same women are less likely to seek care in case of abortion related complications, which may be due service inavailability and/or anticipated poor treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%